Land Value Capture in Urban DRM Programs - Dharmavaram, Soumya (World Bank, Washington, DC, 2013)
Risk-sensitive land use planning is vital for sustainable economic development and effective Disaster Risk Management (DRM). Urban development programs should adopt risk-sensitive land use planning to encourage resilient development guiding the growth of people, assets and services within and away from hazardous zones. Many East Asia and the Pacific (EAP) countries have national land use policy and local plans which incorporate risk assessments; however, they typically lack the means for their implementation and incorporation into development planning. This note introduces the potential of Land Readjustment (LR) and Transfer of Development Rights (TDR) for DRM as seen in their application in Brazil, India, Japan, and the US. The note recommends that if municipalities build capacity for strategic land management, LR and TDR can be used effectively to finance and implement risk-sensitive land use plans. LR offers to accommodate and plan for risks with minimal displacement while TDR promises to equitably relocate development away from hazardous sites through the real estate market.